The influence of teacher training, professional competence, and teacher teaching creativity on student achievement in private junior high schools in Panakukang Makassar - Hajering, Hajering (Jurnal Mirai Management, 2024)
This study aims to determine and analyze the Effect of Teacher Training, Professional Competence and Teaching Creativity on Student Teaching Achievement at UPT SMP Swasta Se Kec Panakukkang. Research shows that on the direct influence, teacher training of UPT SMP Private Kec Panakukkang needs to be improved in professional competence, where there is still low teacher professional competence caused by lack of teacher participation in training, uneven training that is followed, training has not been in accordance with teacher needs so that teachers have not been able to overcome existing problems teaching and learning activities. In addition, teaching creativity also affects student learning achievement, the level of teacher confidence in UPT SMP Private Kec Panakukkang is high so that they are able to make interesting and innovative methods so that students more easily absorb the material. Professional competence as an intervening variable whose role is quite significant in improving learning achievement at UPT SMP Private Kec Panakukkang, can be seen from the lack of mastery of teaching materials, managing learning programs, implementing teaching programs, assessing learning outcomes and mastering educational foundations. Key Words: Teacher Training, Competence, Creativity, Learning Achievement